The Effect of Turmeric (Curcuma domestica) And Papaya Leaves (Carica papaya L.) As Feed Additives on Yolk Color and Yolk Index of Quail Eggs (Cortunix-cortunix japonica) - Novianti, Arindita Niatazya; Rimayanti, Rimayanti; Estoepangestie, A.T. Soelih; Lamid, Mirni; Widjaja, Made Ngakan Rai (Universitas Airlangga, 2025)
The objective of this research was to investigate the effects of turmeric (Curcuma domestica) and papaya leaves (Carica papaya L.) on the yolk color and yolk index of quail eggs (Coturnix coturnix japonica). A total of 24 laying quails were divided into four treatment groups: P0 (standard feed), P1 (feed supplemented with 0.6% turmeric), P2 (feed supplemented with 0.25% papaya leaves), and P3 (feed supplemented with 0.6% turmeric and 0.25% papaya leaves). Yolk color and yolk index measurements were conducted by breaking open the eggs. The yolk color was assessed by comparing the egg yolk with a standardized yolk color fan to identify the closest match. The yolk index was determined by measuring the width of the yolk with calipers and the height of the yolk using a micrometer tripod. Analysis of variance (ANOVA) revealed significant differences among the treatment groups (p < 0.05). The effects of turmeric (Curcuma domestica) and papaya leaves (Carica papaya L.) significantly increased the yolk color and yolk index of quail eggs (Coturnix coturnix japonica).